Research on the symbiosis of sports - characteristic towns and digital technology - Chu, Shaoquan (Quality in Sport, 2025)
In the digital era, the symbiotic development of sports-characteristic towns and digital technology is an essential means to solve the " bottleneck " of the development of sports characteristic towns. This paper discusses how sports-characteristic towns use digital technology to achieve their breakthroughs and expand the application fields of digital technology. This paper’s research methods use the field survey method and the literature data method to carry out research from the three dimensions of the symbiotic unit, symbiotic mode and symbiotic environment. The study finds the relationship between the symbiotic unit and symbiosis in the symbiotic development of sports-characteristic towns and digital technology and the best symbiotic mode. It proposes to improve the stickiness of sports-characteristic towns and symbiotic Internet units, build an ideal symbiotic model of sports-characteristic towns and the Internet, and enhance the stability of sports-characteristic towns and the symbiotic Internet environment.